2019
DOI: 10.1002/cpe.5354
|View full text |Cite
|
Sign up to set email alerts
|

HHFDS: Heterogeneous hybridized fuzzy‐based Dijkstra's multitask scheduling in WSN

Abstract: Summary Wireless Sensor Network (WSN) has to diffuse the independent wireless sensor nodes, which can track the physical or environmental status. In previous works, many issues prevailed with multitask scheduling such as interference, high energy consumption, throughput, etc. Moreover, some issues arise while working with heterogeneous WSN. This work deals with these issues in heterogeneous WSN with aid of the multitask scheduling. For this purpose, a Heterogeneous Hybridized Fuzzy‐based (depends on degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…• There are four ways to extend network life in a heterogeneous sensing node-scheduling method. (i) Design a better sleep strategy [145][146][147][148][149][150]. An efficient sleep strategy can ensure network coverage and connectivity while reducing network energy consumption.…”
Section: Node Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…• There are four ways to extend network life in a heterogeneous sensing node-scheduling method. (i) Design a better sleep strategy [145][146][147][148][149][150]. An efficient sleep strategy can ensure network coverage and connectivity while reducing network energy consumption.…”
Section: Node Schedulingmentioning
confidence: 99%
“…(iv) Provide additional energy replenishment to the network. Due to the development of wireless charging technology, wireless rechargeable sensing systems have become a hot topic of research for scholars at present; such methods can prolong the life of a sensor system simply and effectively, with a wide range of recent literature addressing this topic [145,147,149,150]. • Future energy-saving strategies for heterogeneous sensing systems can be divided into two routes [154].…”
Section: Node Schedulingmentioning
confidence: 99%
“…Since then, numerous schemes have been proposed in different aspects. Schemes for optimizing the maximum capability of the network, heuristic search, transportation efficiency, and implementation of schemes in the evacuation problem have been introduced in this regard. It should be indicated that the integer programming or linear programming method is one of the most adopted schemes in this area, which is widely applied in small‐scale problems.…”
Section: Reviewing the Literaturementioning
confidence: 99%